2020
DOI: 10.3390/cells9041052
|View full text |Cite
|
Sign up to set email alerts
|

Progenitor Cells Activated by Platelet Lysate in Human Articular Cartilage as a Tool for Future Cartilage Engineering and Reparative Strategies

Abstract: Regenerative strategies for human articular cartilage are still challenging despite the presence of resident progenitor cell population. Today, many efforts in the field of regenerative medicine focus on the use of platelet derivatives due to their ability to reactivate endogenous mechanisms supporting tissue repair. While their use in orthopedics continues, mechanisms of action and efficacy need further characterization. We describe that the platelet lysate (PL) is able to activate chondro-progenitor cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 83 publications
2
33
0
Order By: Relevance
“…Although hypACT EVs and blood product promote inflammation indicated by COX2 expression and IL-6 secretion, respectively, this might be beneficial. As low-grade inflammation is characteristic to OA ( Robinson et al, 2016 ) and might trap cartilage regeneration in a self-perpetuating loop, a short-term inflammatory boost might break the vicious circle to allow progression to later stages of wound healing, dampening inflammation and promoting tissue homeostasis, similar to the effects of the platelet secretome including EVs in wounds after blood coagulation and platelet lysate ( Golebiewska and Poole, 2015 ; Nguyen et al, 2018 ; Carluccio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although hypACT EVs and blood product promote inflammation indicated by COX2 expression and IL-6 secretion, respectively, this might be beneficial. As low-grade inflammation is characteristic to OA ( Robinson et al, 2016 ) and might trap cartilage regeneration in a self-perpetuating loop, a short-term inflammatory boost might break the vicious circle to allow progression to later stages of wound healing, dampening inflammation and promoting tissue homeostasis, similar to the effects of the platelet secretome including EVs in wounds after blood coagulation and platelet lysate ( Golebiewska and Poole, 2015 ; Nguyen et al, 2018 ; Carluccio et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed clear clustering of chondrocytes away from both types of MSCs indicating toward less-differentiated nature of both types of MSCs. Recent studies have indicated the existence, within the OA cartilage, of highly proliferative and migrating CPCs (Koelling et al, 2009;Fellows et al, 2017;Carluccio et al, 2020), which could in theory, be shed into the SF and contribute to increased levels of matrix-turnover molecules in SF MSCs. Chondrocyte cultures, which were derived from the full-depth OA cartilage in the present study, could also contain the progeny of these migrating CPCs.…”
Section: Discussionmentioning
confidence: 99%
“…We reported that the platelet factors promoted the activation of the cell proliferation machinery and the cell-cycle re-entry of several types of cells, including chondrocytes and chondroprogenitors [ 18 , 19 , 20 ], human umbilical vein endothelial cells [ 21 , 22 ], bone marrow and umbilical cord mesenchymal stromal cells (MSCs) [ 21 , 23 ], adipose tissue cells [ 21 , 23 , 24 ], and amniotic fluid cells [ 25 ].…”
Section: Introductionmentioning
confidence: 99%